The Epigenetics of Gametes and Early Embryos and Potential Long-Range Consequences in Livestock Species—Filling in the Picture With Epigenomic Analyses - Zhu, Linkai; Marjani, Sadie L.; Jiang, Zongliang (Frontiers in Genetics, 2021)
The epigenome is dynamic and forged by epigenetic mechanisms, such as DNA methylation, histone modifications, chromatin remodeling, and non-coding RNA species. Increasing lines of evidence support the concept that certain acquired traits are derived from environmental exposure during early embryonic and fetal development, i.e., fetal programming, and can even be “memorized” in the germline as epigenetic information and transmitted to future generations. Advances in technology are now driving the global profiling and precise editing of germline and embryonic epigenomes, thereby improving our understanding of epigenetic regulation and inheritance. These achievements open new avenues for the development of technologies or potential management interventions to counteract adverse conditions or improve performance in livestock species. In this article, we review the epigenetic analyses (DNA methylation, histone modification, chromatin remodeling, and non-coding RNAs) of germ cells and embryos in mammalian livestock species (cattle, sheep, goats, and pigs) and the epigenetic determinants of gamete and embryo viability. We also discuss the effects of parental environmental exposures on the epigenetics of gametes and the early embryo, and evidence for transgenerational inheritance in livestock.